PENGARUH MUTU LAYANAN TERHADAP KEPUASAN DI POLIKLINIK HAMIL INSTALASI RAWAT JALAN RUMAH SAKIT UMUM HAJI SURABAYA - Rezky Intan Rahmaningtyas; Stefanus Supriyanto (Universitas Airlangga, 2019)
The number of patient revisits in maternity polyclinic of Surabaya Haji Public Hospital decreased within the period of 2015 – 2016 as much as 24%. In addition, there were several indicators complained by patients in the maternity polyclinic of Surabaya Haji Public Hospital. The purpose of this study was to analyze the effect of service quality to patients’ satisfaction and loyalty in the maternity polyclinic based on Donabedian Theory. It was an observational analytic study, and sampling was taken by simple random sampling technique which in the end obtained a total of 141 respondents. The results of the study indicated that service quality significantly affected patients’ satisfaction. The mean value <3.00 was an issue that should get attention from the polyclinic including structural components (the parking space which is not large and comfortable enough) as well as process components (waiting duration to get services from physicians). Thus, recommendation given to the polyclinic could be to conduct periodic evaluation of the application of service quality as well as patients’ satisfaction and reschedule physicians’ medical practices.